Agihan zakat terhadap asnaf al-Riqāb menurut pandangan ulama dan amalan masa kini - Daud, Mohd Noor; Ismail, Halim (2015)
The study aims to examine the distribution of zakat against asnaf al-Riqāb according to the views of scholars and current practice. This study presents the evidence of the Qur'an, al-Sunnah and the debate among scholars on the distribution of zakat against asnaf al-Riqāb and its implementation in Malaysia. This study was conducted using qualitative research methods and analyzed using deductive, inductive and comparative methods. The results of the study show that the distribution of zakat against asnaf al-Riqāb should be implemented nowadays to expel Muslims who are bound by various forms of slavery. Recent issues relating to asnaf al-Riqāb are like captive and kidnapping issues among Muslims, Muslims trapped by immoral practices such as prostitution, drug addiction and alcohol addiction and are plagued under the control of a ruthless ruler, then the distribution of zakat against asnaf al-Riqāb is very much worth noting.